Asuhan Kebidanan Komprehensif Pada Ibu Hamil Keputihan Dan Nyeri Perut Dengan Penerapan Asuhan Kebidanan Komplementer Terintegrasi - Wulandari, Hani; Nilawati, Iin; Elly, Nur (Jurnal Kebidanan Manna, 2022)
Continuity of Care (COC) midwifery care is continuous midwifery care from pregnancy to family planning as an effort to reduce Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR). ANC has been carried out according to standards both in quantity and quality and the problem of vaginal discharge and abdominal pain is resolved with Continuity Of Care (COC) and complementary care. The implementation of the care given to Mrs. "F" was in accordance with the predetermined plan, ANC was carried out 9 times at PBM, during pregnancy in TM I the mother complained of nausea, in TM II she complained of vaginal discharge and abdominal pain and was given complementary midwifery care interventions with betel leaf boiled water for 14 weeks. days and vaginal discharge could be resolved on the second visit, while complaints of lower abdominal pain were given complementary therapy with warm water compresses. In labor, the mother gave birth with sectio Caesarea surgery so that the author could not provide the planned complementary care intervention, namely the provision of nabees dates and massage counter pressure. Babies born fit BB 3300 grams and PB 50 cm and IMD was not carried out, complementary therapies were given, namely baby massage and murrotal therapy. Postpartum care runs normally. Complementary care is provided, namely the provision of banana heart nutrition and oxytocin massage, but does not do pain management with the massese because the mother does not feel significant pain. Mother decided on the MAL method even though she had been directed and given MKJP counseling care. After the author conducted midwifery care for Mrs. “F” during pregnancy, there was no discrepancy between theory and case. In the delivery care, the mother gave birth by Sectio Caesarea and there were no complications, complementary care was not given, the neonatal period, the postpartum period were running normally and complementary care was given but counter pressure massage was not given. During the neonate, puerperium, and family planning, all were within normal limits. It is hoped that the owner of the practice land can perform Continuity Of Care (COC) midwifery care and provide complementary midwifery care as a solution to overcome maternal complaints such as vaginal discharge with water boiled betel leaf and lower abdominal pain with warm water compresses.